2013
DOI: 10.1158/1078-0432.ccr-13-1151
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Enzyme AKR1C3 Is a Novel Androgen Receptor-Selective Coactivator that Promotes Prostate Cancer Growth

Abstract: Purpose: Castration-resistant prostate cancer (CRPC) may occur by several mechanisms including the upregulation of androgen receptor (AR), coactivators, and steroidogenic enzymes, including aldo keto reductase 1C3 (AKR1C3). AKR1C3 converts weaker 17-keto androgenic precursors to more potent 17-hydroxy androgens and is consistently the major upregulated gene in CRPC. The studies in the manuscript were undertaken to examine the role of AKR1C3 in AR function and CRPC.Experimental Design: LNCaP cells stably transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 31 publications
3
84
0
1
Order By: Relevance
“…Notably, it was recently reported that AKR1C3 (WT or CI mutant) could function as an AR co-activator (52), another example of a catalytically independent role of AKR1C3 on AR activity. Therefore, identification of mechanisms underlying the noncatalytic function of AKR1C3 may provide new targets for development of novel AKR1C3 inhibitors that complement inhibitors targeting AKR1C3 catalytic activity as potential CRPC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was recently reported that AKR1C3 (WT or CI mutant) could function as an AR co-activator (52), another example of a catalytically independent role of AKR1C3 on AR activity. Therefore, identification of mechanisms underlying the noncatalytic function of AKR1C3 may provide new targets for development of novel AKR1C3 inhibitors that complement inhibitors targeting AKR1C3 catalytic activity as potential CRPC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…GTX-560, a potent competitive inhibitor of AKR1C3, revealed for the first time that this compound could block the hitherto unrecognized AR co-activator function of AKR1C3 suggesting that the compound would have added benefit in the treatment of CRPC patients [74]. GTx-560 was also found to have antitumor activity in prostate cancer cell xenograft models of CRPC.…”
Section: 0 Approaches To Counter Drug Resistancementioning
confidence: 99%
“…Isoquinolines represented by the lead compound GTX-560 27 not only act as competitive inhibitors of AKR1C3 but also block its AR coactivator function which was previously unknown [58]. The isoquinolines were claimed in patents WO2013142390 and WO2014039820A1 filed by GTx-Therapeutics.…”
Section: Chemistrymentioning
confidence: 99%